Reversible control of series-excitated DC motors - Sinyavsky, O.; Savchenko, V.; Prudnikova, N. (Energy and Automation, 2025)
Series-excited DC motors are used in electric drives of mobile machines, electric vehicles and machines that operate with significant overloads.These motors have a nonlinear magnetization curve. Therefore, it is impossible to analytically describe the mechanical and electromechanical characteristics. For this, the motor magnetization curve (transition characteristic) is experimentally determined.The motor is reversed through the anti-switching braking mode. into the anti-switching braking mode, which necessitates the inclusion of an additional braking resistor in the armature circuit. After anti-switching braking, the motor begins to rotate in the other direction. In this case, it is necessary to limit the starting current of the motor by introducing additional resistances.The purpose of the study is to develop schemes for reversing control of series-excited DC motors and methods for analytical determination of starting and braking resistances.Currently, the most common in counter-switching braking schemes is control in the EMF function, and when starting the motor – in the current function.A scheme for reversing control of a series-excited DC motor with counter-switching braking in the EMF function and engine starting in the time function has been developed. A scheme is also presented that provides only engine braking in the EMF function.A method for analytical determination of starting resistances for braking resistances for the developed control schemes has been developed.Key words: series-excited DC motor, reversing, counter-switching braking, motor starting, starting resistors